Baitul Mal Qanun as An Instrument for Economic Development in Aceh: A SWOT Analysis - Akmal; Nurhayati; Saparuddin Siregar (Journal of Islamic Economics and Business, 2025)
This study aims to analyze the implementation of Qanun No. 3 of 2021 concerning Baitul Mal in Aceh Province using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to evaluate its contribution to economic development, particularly in poverty alleviation, MSME empowerment, and improving community welfare. The research employs a descriptive qualitative method by collecting data from the annual reports of Baitul Mal Aceh, BPS Aceh statistics, and in-depth interviews with Islamic economic experts and stakeholders. The findings reveal that the Qanun provides a strong legal framework; however, zakat collection has only reached 6% of the potential IDR 1.5 trillion in 2024, limiting its impact on poverty reduction (a decline from 15% in 2023 to 14.5% in 2024). The productive zakat program has proven to increase beneficiaries’ income by 15% (IDR 14.13 billion distributed to 4,895 MSMEs), although unequal distribution and limited human resources remain major constraints. The study implies the need for institutional reform of Baitul Mal by enhancing transparency, digitalization, and inter-unit coordination. Policy recommendations include the development of a digital zakat platform, training 200 certified amil between 2025–2027, and harmonizing fiscal policies with the central government to recognize zakat as a deductible from income tax.